Silver economy as a response to demographic changes - Leśna-Wierszołowicz, Elwira (Srebrna gospodarka jako odpowiedź na zmiany demograficzne, 2018)
The aim of the article is to present the essence of the silver economy, which means economic activity aimed at satisfying the needs of ageing society. The article describes the ageing process of the Polish society which is the result of decline in fertility and lengthening of life expectancy. The phenomenon of demographic aging can be a great opportunity for business and economy. The article introduces the concept and main assumptions of the silver economy. The main idea of the silver economy is that supplying goods and services for the growing sector of elderly consumers can stimulate economic growth and create new jobs. According to the silver economy principles, older people are perceived as an active, productive and socially useful group. In Poland undertaking activities in the field of the silver economy may be a positive economic stimulus, which will contribute to the expansion of services and products offered to the elderly, especially those that remain in a favorable financial situation. The key element of the silver economy is gerontechnology. Gerontechnology is an interdisciplinary field combining gerontology and technology. Gerontechnology concerns matching technological environments to housing, health, mobility, communication, leisure and work of older people
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 529; s. 162-169
Keywords: aging of society; demographic changes; silver economy; starzenie się społeczeństwa; przemiany demograficzne; srebrna gospodarka